Electroplated and cast double crown-retained removable dental prostheses: 6-year results from a randomized clinical trial - Stober, Thomas; Lorenzo Bermejo, Justo; Séché, Anne-Christiane; Lehmann, Franziska; Rammelsberg, Peter; Bömicke, Wolfgang (Clinical oral investigations, 2015)
ObjectivesThe purpose of this study was to evaluate the clinical performance of removable dental prostheses (RDP) supported by either electroplated (EP-RDP) or cast (C-RDP) double crowns.Material and methodsFifty-four participants received a total of 60 RDP. Two hundred and seventeen abutment teeth were provided with double crowns. The participants were randomly assigned to two groups (EP-RDP or C-RDP). Re-evaluations took place after 6 months and then once a year up to 6 years. Primary endpoint was survival time for RDP and abutment teeth; secondary endpoints were failure of facing, decementation of primary crown, and post-prosthetic endodontic treatment. T, U, and chi-squared tests were used to assess the homogeneity of the EP-RDP and C-RDP groups. Survival differences were analyzed with log-rank tests and Cox regression models; secondary endpoints were assessed by the use of logistic regression.ResultsSix-year survival was 77 % for EP-RDP and 97 % for C-RDP. Cumulative survival of abutment teeth was 85 % for EP-RDP and 91 % for C-RDP; differences between survivals in the two groups did not reach statistical significance. Survival of abutment teeth depended on tooth vitality. Failures of facings, decementations, or post-prosthetic endodontic treatments were not different between groups.ConclusionsTo identify possible differences between different double crown systems, longer follow-up periods and/or larger numbers of patients are needed.Clinical relevanceSurvival of teeth supporting double crown-retained RDP is affected by their vitality. Clinical performance was acceptable for both RDP supported by electroplated or cast double crowns.